2015
DOI: 10.1021/acs.jproteome.5b00508
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Verification of Membrane Proteins as Potential Therapeutic Targets Located in the 11q13 Amplicon in Cancers

Abstract: Tumor types can be defined cytologically by their regions of chromosomal amplification, which often results in the high expression of both mRNA and proteins of certain genes contained within the amplicon. An important strategy for defining therapeutically relevant targets in these situations is to ascertain which genes are amplified at the protein level and, concomitantly, are key drivers for tumor growth or maintenance. Furthermore, so-called passenger genes that are amplified with driver genes and a manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…The FGF19 genomic locus is on the chromosome 11q13.3, and is frequently amplified in human cancers. For example, amplification of the FGF19 genomic locus including the wellestablished proto-oncogene CCND1, was found in liver cancer, breast cancer, lung cancer, bladder cancer and esophageal cancer (Sawey et al, 2011;Hoover et al, 2015;Tiong et al, 2016;Zhang et al, 2017). Hyperactivation of FGFR4 by FGF19 was reported in colon cancer cells and hepatocellar carcinoma.…”
Section: Molecular Characteristics Of Fgf19mentioning
confidence: 99%
“…The FGF19 genomic locus is on the chromosome 11q13.3, and is frequently amplified in human cancers. For example, amplification of the FGF19 genomic locus including the wellestablished proto-oncogene CCND1, was found in liver cancer, breast cancer, lung cancer, bladder cancer and esophageal cancer (Sawey et al, 2011;Hoover et al, 2015;Tiong et al, 2016;Zhang et al, 2017). Hyperactivation of FGFR4 by FGF19 was reported in colon cancer cells and hepatocellar carcinoma.…”
Section: Molecular Characteristics Of Fgf19mentioning
confidence: 99%
“…Amplification of the 11q13 amplicon is one of the most common events in cancer and has a well-recognized role in carcinogenesis of several tumours including head and neck and breast cancers [ 43 ]. The 11q13 amplicon contains Cyclin D1 which is a known oncogene but also FGF19, FGF23 and ANO1 which are tumour promoting genes.…”
Section: Role Of Fgf 19-fgfr4 Pathway In Hepatocellular Carcinogenmentioning
confidence: 99%
“…CD109 is potentially advantageous for drug development not only based on its expression on the cell surface and ability to bind the anti‐CD109 antibody in vivo but also because CD109‐deficient mice exhibit no lethal phenotype, with no significant difference in life span between WT and CD109‐deficient mice . Although there are no reports that the anti‐CD109 antibody acts as a therapeutic agent in vivo, one study showed that CD109 expression was sufficient to induce antibody internalization and cell killing in 11q13‐amplified cell lines via an antibody/drug‐conjugate approach . Further research is needed to develop tumor treatments involving antibody based drugs targeting CD109.…”
Section: Cd109 Is a Membrane Protein Expressed In Malignant Tumorsmentioning
confidence: 99%
“…8 Although there are no reports that the anti-CD109 antibody acts as a therapeutic agent in vivo, one study showed that CD109 expression was sufficient to induce antibody internalization and cell killing in 11q13amplified cell lines via an antibody/drug-conjugate approach. 61 Further research is needed to develop tumor treatments involving antibody based drugs targeting CD109.…”
Section: Further Questions and Perspectivesmentioning
confidence: 99%